Myths about violence among judiciary professionals - Srna Jelena; Tenjović Lazar (Temida)
The presence of myths about violence (mistaken, but resilient and broadly shared opinions) among those professionals who deal with violence in their work could interfere with their educational advancement and professional development. The goal of the research was to explore the presence and spread ability of the different kind of myths about violence among judiciary professionals. The method: This research was carried out within the framework of a specialist education on children rights for the family court judges. The questionnaire for the detection of myths was constructed on the basis of educational material and the data was collected at the beginning of the education process. The data have gathered from the 175 judiciary professionals. The results indicate that among the judiciary professionals a relatively small number of myths, related primarily to the causes and consequences of violence, is present. We found those results useful for the advancement of professional training and for the stimulation of similar research in the frame of the educational and intervention work of those experts. .